Tuberculosis Awareness Program and Associated Changes in Knowledge Levels of School Students - Gothankar, Jayashree S (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: This study aimed to assess the effectiveness of tuberculosis awareness program amongst school students. METHODS: This school-based interventional study was done on 135 secondary school students. They were randomly selected in field practice area of Urban Health Training Center (UHTC) of a private medical college in Pune city. Health awareness session on tuberculosis was conducted by using various visual and audiovisual aids by the medical college undergraduate students. A pre-test and post-proforma was filled before and after the session. Paired t-test was used to assess the effectiveness of awareness program. RESULTS: There was a highly significant (P = 0) increase in the knowledge of school students after the tuberculosis awareness program by medical undergraduate students. The mean pre-test scores were 6.31 (52.58%), and the mean post-test scores were 10.20 (85%). This activity also helped medical undergraduate students to acquire skills related to communication, working in a team, preparation and presentation of various visual aids for health awareness program; they also gained knowledge of research methodology. CONCLUSIONS: Health education program by medical students helped significantly to improve the knowledge of school students regarding tuberculosis. Thus, medical college students can be involved to some extent for conducting health-related behavioral change communication (BCC) activities in schools during their Community Medicine morning posting. Collaboration of private medical colleges, schools, and district tuberculosis units (DTUs) can be ideally achieved under public private partnership (PPP) for health awareness programs.